Violência religiosa no ensino de história: renovação carismática católica contra as religiões de matrizes africanas no Brasil e em Moçambique - Paulo, Adriano Ferreira de (2020)
The discussions and manifestations of religious intolerance in contemporary social contexts have been the subject of debates about their problems in educational contexts, with the school being one of the main places to suffer the influence of this ethnic-religious violence. Thus we aim in this research to address the issue, giving voice to the concrete clashes and conflicts expressed within the scope of the Catholic Charismatic Renewal (RCC) and the New Communities in the city Fortaleza (Brazil) and Maputo (Mozambique). We analyze religious violence in public schools, particularly when the Catholic Charismatic Renewal and New Communities turn against religions of African origin, in the context of teaching history in basic education. We start from the criticism of intolerances manifested in the scope of school life, in relation to religions of African origin, suggesting possibilities for multicultural studies and interreligious dialogue, as possible ways of solving them, with a view in order to comply with law 10.639 / 03 and promote an appreciation of Afro-Brazilian and African culture. Our theoretical foundation is primarily based on some authors such as Goffman (1988), Bourdieu; Passerron (1992), Miranda (1999), Freire (2002), Martinez (2004), Sodré (2012), Basílio (2015), Chiziane (2015), Berger (2017), Schwartz (2019), among others. This qualitative research elects Participant Research as a methodology (SCHMIDIT, 2006), and focuses on the scenario of five public schools in the city of Fortaleza (Brazil) and five in Maputo (Mozambique), in the current historical time. The subjects of this research, being teachers of History of the 7th year (or 7th cycle) of basic education, enabled us to conclude that, among the obstacles that charismatic thinking brings to education, we see the restriction of multicultural relations, due mainly to the naturalization of religious violence, as well as due to the limits that the discriminatory view shows, in the actual implementation of the teaching-learning process of history. For both countries, we recommend pedagogical actions that put into practice the emphasis on intercultural multiculturalism, as well as interreligious dialogue, for the purpose of a cultural diversity that builds critical theoreticalpractical actions in learning, making it possible to stop the religious violence that arises. in the intolerances that mediate the coexistence of school culture.